2007
DOI: 10.1111/j.1365-2583.2007.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

The nicotinic acetylcholine receptor subunits Mdα5 and Mdβ3 on autosome 1 of Musca domestica are not involved in spinosad resistance

Abstract: Spinosad is a relatively new insecticide that exerts its toxic action via nicotinic acetylcholine receptors (nAChRs). Spinosad resistance in house flies appears to be due to an altered target site. To evaluate the molecular basis of spinosad resistance, two nAChR subunit genes, Mdalpha5 and Mdbeta3 were cloned and characterized from an insecticide-susceptible (aabys) and spinosad resistant (rspin) strain of the house fly, Musca domestica. The Mdalpha5 and Mdbeta3 cDNAs encode proteins of 781 and 432 amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…We previously identified 12, 13, one and zero A-to-I RNA editing sites in house fly Mda6, Mda5, Mda2, Mdb3, respectively. [38][39][40] The sites of RNA editing for a6 subunit genes are conserved between D. melanogaster, M. domestica and H. virescens. 34,40,41) RNA editing is not randomly distributed across nAChR subunits, nor are the regions of the protein that have resulting amino acid substitutions the same between different subunits.…”
Section: Genomics Of Nachr Subunit Genesmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously identified 12, 13, one and zero A-to-I RNA editing sites in house fly Mda6, Mda5, Mda2, Mdb3, respectively. [38][39][40] The sites of RNA editing for a6 subunit genes are conserved between D. melanogaster, M. domestica and H. virescens. 34,40,41) RNA editing is not randomly distributed across nAChR subunits, nor are the regions of the protein that have resulting amino acid substitutions the same between different subunits.…”
Section: Genomics Of Nachr Subunit Genesmentioning
confidence: 99%
“…For example, A-to-I editing ranged from 3% to 100% at different sites within Mda5. 38) Grauso et al first investigated A-to-I editing in the nAChR family and found seven edited sites in Da6 from D. melanogaster. 41) Hoopengardner et al 45) further identified seven, four and two A-to-I RNA editing sites in Da5, Db1 and Db2, respectively.…”
Section: Genomics Of Nachr Subunit Genesmentioning
confidence: 99%
See 3 more Smart Citations